Preparing Students for the Development of Musical Talent of the Child in the Process of Vocal and Choral Activity: Array - Sirotkina, Zhanna; Chebotar, Lyudmila (Journal of Danubian Studies and Research, 2020)
In the new socio-economic conditions of the development of our society, the problem of studying children’s giftedness has become one of the priority research areas. Talent in different areas manifests itself in certain age periods. According to many observations, the talent for museums and fine arts can manifest itself much earlier than the giftedness to other activities. Musical giftedness is one of the special types of giftedness. This can occur in children even in preschool age. Musical talent is characterized by the presence of musicality. We decided to study how vocal and choral activities will influence the development of a child’s musical talent.